2012
DOI: 10.1177/1947603511433181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Platelet-Rich Plasma Composition on Anabolic and Catabolic Activities in Equine Cartilage and Meniscal Explants

Abstract: Objective:To evaluate the effects of single- and double-spin preparations of platelet-rich plasma (PRP) on anabolic and catabolic activities of cartilage and meniscal explants in vitro.Methods:Single- and double-spin PRP was prepared using laboratory processing or commercial kits. The cellular contents were quantified, and each PRP was mixed in equal quantities with cell culture medium and added to cartilage or meniscus explant cultures, with or without interleukin 1 β (IL-1β). Extracellular matrix synthesis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 35 publications
(56 reference statements)
1
50
2
4
Order By: Relevance
“…The cellular components of PRP products are a differentiating factor that may influence the clinical effectiveness of their administration for the treatment of a disease and/or the regeneration of damaged tissue. Several studies support the use of P‐PRP in a large number of pathologies of the musculoskeletal system . Other clinical studies have reported the occurrence of adverse effects after the administration L‐PRP .…”
Section: Discussionmentioning
confidence: 88%
“…The cellular components of PRP products are a differentiating factor that may influence the clinical effectiveness of their administration for the treatment of a disease and/or the regeneration of damaged tissue. Several studies support the use of P‐PRP in a large number of pathologies of the musculoskeletal system . Other clinical studies have reported the occurrence of adverse effects after the administration L‐PRP .…”
Section: Discussionmentioning
confidence: 88%
“…As mentioned, there are controversial opinions regarding which is the ideal concentration of PLT and WBC in PRP to be used for therapeutic aims in patients with OA [20]. This in vitro research was conducted to complement previous studies [22,[24][25][26] of in vitro cartilage response to several concentrations (25% and 50%) of PRG supernatants from two different PRP preparations (P-PRP and L-PRP).…”
Section: Discussionmentioning
confidence: 94%
“…These complex mechanisms are constantly reported in several studies evaluating the in vitro effects of several PRP preparations and related substances in in vitro systems of joint cell (tissue) inflammation [24,26,34,36].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, there are several in vitro studies in horses that show the positive effect of leukoreduced PRP (also known as pure PRP [P-PRP]) preparations in musculoskeletal tissues in contrast to leukoconcentrated PRP (L-PRP) preparations (Kisiday et al 2012, McCarrel et al 2012, Boswell et al 2014.…”
Section: Introductionmentioning
confidence: 99%